2018
DOI: 10.1186/s12866-018-1288-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity obtained by culturable approaches in the gut of Glossina pallidipes population from a non sleeping sickness focus in Tanzania: preliminary results

Abstract: BackgroundGlossina pallidipes is a haematophagous insect that serves as a cyclic transmitter of trypanosomes causing African Trypanosomiasis (AT). To fully assess the role of G. pallidipes in the epidemiology of AT, especially the human form of the disease (HAT), it is essential to know the microbial diversity inhabiting the gut of natural fly populations. This study aimed to examine the diversity of G. pallidipes fly gut bacteria by culture-dependent approaches.Results113 bacterial isolates were obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…lecticularia . Dietzia has been described from other triatomine species [ 40 , 41 , 43 , 46 , 47 , 51 ] and other hematophagous insects ( Aedes albopictus [ 110 ], Glossina pallidipes [ 111 ]), suggesting it may be an important mutualist. However, unlike typical primary symbionts, Dietzia does not seem to be transmitted vertically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…lecticularia . Dietzia has been described from other triatomine species [ 40 , 41 , 43 , 46 , 47 , 51 ] and other hematophagous insects ( Aedes albopictus [ 110 ], Glossina pallidipes [ 111 ]), suggesting it may be an important mutualist. However, unlike typical primary symbionts, Dietzia does not seem to be transmitted vertically.…”
Section: Discussionmentioning
confidence: 99%
“…In our results, Dietzia, a bacterium closely related to Rhodococcus [109], is the dominant bacterium in late instars of T. rubida, T. protracta, and T. lecticularia. Dietzia has been described from other triatomine species [40,41,43,46,47,51] and other hematophagous insects (Aedes albopictus [110], Glossina pallidipes [111]), suggesting it may be an important mutualist. However, unlike typical primary symbionts, Dietzia does not seem to be transmitted vertically.…”
Section: Dominant Taxa and Endosymbiosismentioning
confidence: 99%
“…The microbes found on Assam tea leaf surfaces revealed an abundance of Actinobacteria, Firmicutes, and Proteobacteria phyla, which have been commonly found in the environment including soils, leaves, stems, and roots, as well as skin of human and animals [ 66 ]. In this study, all diversity indices indicated that Phayao province had the highest bacterial biodiversity, while Phrae province had the lowest.…”
Section: Discussionmentioning
confidence: 99%
“…In our results, Dietzia, a bacterium closely related to Rhodococcus [93], is the dominant bacterium in late instars of T. rubida, T. protracta, and T. lecticularia. Dietzia has been described from other triatomine species [33,35,36,[42][43][44] and other hematophagous insects (Aedes albopictus [94], Glossina pallidipes [95]), suggesting it may be an important mutualist. However, unlike typical primary symbionts, Dietzia does not seem to be transmitted vertically.…”
Section: Dominant Taxa and Endosymbiosismentioning
confidence: 99%